ОБСЕ Insights 2020 Коронавирус, война, кризис лидерства - Institut für Friedensforschung- und Sicherheitspolitik (IFSH) (Nomos Verlagsgesellschaft mbH & Co. KG, 2021)
The contributions to the 2020 edition of OSCE Insights examine the various crises the OSCE faced during that year. Themes include the efforts of the Minsk Group to manage the conflict over Nagorno-Karabakh and the implications of anti-coronavirus measures for the OSCE Code of Conduct on Politico-Military Aspects of Security. Furthermore, authors analyse OSCE conflict cycle tools, the OSCE's role in the fight against antisemitism, the increasingly limited space for supporting democratic police governance in Central Asia, trust-building in the field of arms control, societal views on the conflict in Eastern Ukraine, relations between the OSCE and the Council of Europe, and Kazakhstan's aspirations for hosting a connectivity center.